2016
DOI: 10.1080/15384047.2016.1220453
|View full text |Cite
|
Sign up to set email alerts
|

Complete and sustained response of adult medulloblastoma to first-line sonic hedgehog inhibition with vismodegib

Abstract: Medulloblastoma is an aggressive primitive neuroectodermal tumor of the cerebellum that is rare in adults. Medulloblastomas fall into 4 prognostically significant molecular subgroups that are best defined by experimental gene expression profiles: the WNT pathway, sonic hedgehog (SHH) pathway, and subgroups 3 and 4 (non-SHH/WNT). Medulloblastoma of adults belong primarily to the SHH category. Vismodegib, an SHH-pathway inhibitor FDA-approved in 2012 for treatment of basal cell carcinoma, has been used successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…2). Importantly, PTCH1 oncogenic mutations are described as actionable gene mutations for SMO-inhibitors vismodegig and sonidegib (in clinical trials for recurrent or refractory MB showing encouraging results) [31][32][33][34] . It is also important to highlight the CNV landscape (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2). Importantly, PTCH1 oncogenic mutations are described as actionable gene mutations for SMO-inhibitors vismodegig and sonidegib (in clinical trials for recurrent or refractory MB showing encouraging results) [31][32][33][34] . It is also important to highlight the CNV landscape (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Only five recent patients had molecular testing: 1 WNT, 2 SHH (1 TP53 wild-type, 1 TP53 mutated) and 2 non-WNT/non-SHH. SHH-pathway inhibitors are currently being evaluated in phase I–III trials, and may provide a therapeutic option to chemoradiation protocols currently used for these patients [7, 44]. Despite advances in subtyping, it remains difficult to assess prognosis in adult MB since studies have reported heterogenous treatment, many without chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, there are many Smo inhibitors have been under investigation in clinical trials. Among them, GDC-0449 (vismodegib) was approved by FDA for treatment of advanced BCC in 2012 (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%